2021
DOI: 10.1016/j.cub.2021.08.050
|View full text |Cite
|
Sign up to set email alerts
|

The BES1/BZR1-family transcription factor MpBES1 regulates cell division and differentiation in Marchantia polymorpha

Abstract: The BES1/BZR1-family transcription factor MpBES1 regulates cell division and differentiation in Marchantia polymorpha Graphical abstract Highlights d MpBES1 is the closest homolog of angiosperm BEH proteins in Marchantia polymorpha d MpBES1 plays a key role in meristem cell division and differentiation in Marchantia d MpBES1 behaves as a gain-of-function form when expressed in Arabidopsis thaliana d BR signaling likely co-opted this module, introducing new regulatory checkpoints

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Due to the complexity of fern genomes and the immaturity of transformation technology, it remains challenging to create mutants. Recently, it was reported that when the BZR1/BES1 family gene of Marchantia polymorpha was knocked out, the growth was significantly reduced, indicating that the BZR1/BES1 component plays an important role in the growth and development of Marchantia polymorpha [ 47 ]. Based on this, we speculate that BR signaling in ferns plays an important role and that their specific biological functions need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of fern genomes and the immaturity of transformation technology, it remains challenging to create mutants. Recently, it was reported that when the BZR1/BES1 family gene of Marchantia polymorpha was knocked out, the growth was significantly reduced, indicating that the BZR1/BES1 component plays an important role in the growth and development of Marchantia polymorpha [ 47 ]. Based on this, we speculate that BR signaling in ferns plays an important role and that their specific biological functions need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…MpBES1 phosphorylation by MpGSK was much weaker than the phosphorylation of BES1/BZR1 by BIN2 (Mecchia et al 2021). Moreover, the interaction between MpBES1 and MpGSK was not stronger as that between BES1 and BIN2 or MpGSK in yeast two-hybrid system (Mecchia et al 2021). However, the phenotypes of both Mpbes1 and Mpgsk show same trend in terms of repression of the cell differentiation, suggesting that MpBES1 is one of possible candidates for substrate of MpGSK in M. polymorpha.…”
Section: Mpgsk Regulates the Cell Proliferation And Differentiation F...mentioning
confidence: 96%
“…A single GSK3-like kinase, MpGSK (Mp7g04170; Supplementary Figure S2A), was identified in the genome of M. polymorpha (MarpolBase genome database [v5.1: http://marchantia. info]; Mecchia et al 2021;Montgomery et al 2020). MpGSK has a highly conserved serine/threonine protein kinase domain including the activation loop and the TREE domain for the proteasome-mediated protein degradation (Peng et al 2008), as other plant GSK3s possess (Supplementary Figure S2B).…”
Section: Polymorpha Has a Single Gsk3-like Kinase Orthologmentioning
confidence: 99%
See 2 more Smart Citations